A case study of the Methodist Church in the light of Luke 18:1–8 to address the plight of women - Peter Masvotore (HTS Teologiese Studies/Theological Studies, 2024)
As much as Zimbabwe is considered one of the highly literate countries in the Global South, with well documented succession and inheritance laws, womenfolk continue to be stripped of their assets after the death of their husbands. This trend became even worse during the peak of the COVID-19 pandemic when movement was restricted, making it difficult to access the courts of law. Using a mixed methodological approach of a desk research and qualitative interviews conducted in the Methodist Church in Zimbabwe, Zororo Comfort circuit in Harare, it has been noted that women and girls face numerous horrific experiences, pushing them to wallow in the margins of society. This study therefore calls for the church to address the vulnerability of women and girls using a deviant theory. To date, there are increasing figures of domestic violence, sexual assault, and child marriages. Financial and communal disturbances corresponding through continuous pandemic challenges for women are aggravated, and those who survive find it challenging to hunt for fairness because of stockpiled court issues and freedom for the perpetrators. The fact that women are dispossessed of their belongings because of the cultural status of being a woman calls for a cultural cue. Using a deviant theory in the narrative of a tenacious widow in the gospel of Luke 18:1–8 from a sociological dimension, this study provides a critical edge into interpreting the action of this widow who deviated from expected societal customs. The study concludes by calling faith communities to re-read the widow’s story through deviant theory spectacles to raise questions on how this widow courageously represented herself from societal margin to undermine the centre (patriarchal standards) and to utilise the text as a resource for addressing the plight of women to be repositioned and be empowered in Zimbabwe.